2021
DOI: 10.1016/j.puhip.2021.100157
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among Bangladeshi Youth during the early stage of the COVID-19 pandemic: A single-site survey

Abstract: Objectives This study aimed to determine the impact of the COVID-19 pandemic on the psychological, mental health and quality of life among Bangladeshi residents. Study design A purposive cross-sectional study of quality of life during the COVID-19 pandemic was performed. Methods Respondents completed a modified questionnaire that determined the Impact of Event Scale (IES), indicators of psychological distress impact, impact on government stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Similarly, the COVID-19 pandemic has hurt the quality of life of these populations. A study with the Bangladeshi residents found that more than 50% of respondents had decreased quality of life, mainly due to difficulties in meeting their basic needs, loss of jobs and barriers to accessing education ( Mondal et al, 2021 ). A study in China found that 41.3% of people had depressive symptoms and a significantly lower quality of life ( Ma et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the COVID-19 pandemic has hurt the quality of life of these populations. A study with the Bangladeshi residents found that more than 50% of respondents had decreased quality of life, mainly due to difficulties in meeting their basic needs, loss of jobs and barriers to accessing education ( Mondal et al, 2021 ). A study in China found that 41.3% of people had depressive symptoms and a significantly lower quality of life ( Ma et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Students graduating in 2020 missed several job postings. Recent experiences suggest that academic failures or interruptions disproportionately affect low-income students resulting in youth antisocial behavior and societal instability (Mondal et al, 2021). In this COVID-19 pandemic, students who have no internet access signify that the level of poverty in the community upsurges and the rate of access to the internet have fallen swiftly and those students who do not have a low socio-economic capacity to afford broadband are at greatest risk for falling behind or facing other hurdles for online learning.…”
Section: Problem Statementmentioning
confidence: 99%
“…Global prevalence of elevated mental health struggles is evident since the onset of the pandemic 1 . A cross‐sectional study comprising 465 young individuals with no history of mental health illnesses, depicted more than half of them experiencing feelings of severe anxiety and decline in the quality of life during the early phase 2 . A definite and mild impact of the pandemic on physical and psychological stress was thus reported 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A cross‐sectional study comprising 465 young individuals with no history of mental health illnesses, depicted more than half of them experiencing feelings of severe anxiety and decline in the quality of life during the early phase 2 . A definite and mild impact of the pandemic on physical and psychological stress was thus reported 2 . Several studies and reviews have confirmed healthcare workers (HCWs) experiencing greater instances of stress, burnout and mental illnesses 3–5 .…”
Section: Introductionmentioning
confidence: 99%